Red blood cell distribution width combined with age as a predictor of acute ischemic stroke in stable COPD patients - Cai, Shikun; Li, Yao; Sun, Bo; Wang, Kai; Wan, Zongren; Yang, Dan; Tian, Xiangyang; Wu, Liao; Zhu, Rong (Frontiers in Neurology, 2023)
Aim: The aim of this retrospective study was to investigate the independent clinical variables associated with the onset of acute cerebral ischemic stroke (AIS) in patients with stable chronic obstructive pulmonary disease (COPD). Method: A total of 244 patients with COPD who had not experienced a relapse within 6 months were included in this retrospective study. Of these, 94 patients hospitalized with AIS were enrolled in the study group, and the remaining 150 were enrolled in the control group. Clinical data and laboratory parameters were collected for both groups within 24 hours after hospitalization, and the data of the two groups were statistically analyzed. Results: The levels of age, white blood cell (WBC), neutrophil (NEUT), glucose (GLU), prothrombin time (PT), albumin (ALB), and red blood cell distribution width (RDW) were different in the two groups (P < 0.01). Logistic Regression Analysis showed that age, WBC, RDW, PT, and GLU were independent risk factors for the occurrence of AIS in patients with stable COPD. Age and RDW were selected as new predictors, and the receiver operating characteristic curves (ROC) were plotted accordingly. The areas under the ROC curves of age, RDW, and age + RDW were 0.7122, 0.7184, and 0.7852, respectively. The sensitivity was 60.5%, 59.6%, and 70.2%, and the specificity was 72.4%, 86.0%, and 60.0%, respectively. Conclusion: The combination of RDW and age in patients with stable COPD might be a potential predictor for the onset of AIS.